Independent nucleation and heterogeneous assembly of structure during folding of equine lysozyme. - Morozova-Roche, L; Jones, J; Noppe, W; Dobson, C (1999)
The refolding of equine lysozyme from guanidinium chloride has been studied using hydrogen exchange pulse labelling in conjunction with NMR spectroscopy and stopped flow optical methods. The stopped flow optical experiments indicate that extensive hydrophobic collapse occurs rapidly after the initiation of refolding. Pulse labelling experiments monitoring nearly 50 sites within the protein have enabled the subsequent formation of native-like structure to be followed in considerable detail. They reveal that an intermediate having persistent structure within three of the four helices of the alpha-domain of the protein is formed for the whole population of molecules within 4 ms. Subsequent to this event, however, the hydrogen exchange protection kinetics are complex and highly heterogeneous. Analysis of the results by fitting to stretched exponential functions shows that a series of other intermediates is formed as a consequence of the stepwise assembly of independently nucleated local regions of structure. In some molecules the next step in folding involves the stabilisation of the remaining helix in the alpha-domain, whilst in others persistent structure begins to form in the beta-domain. The formation of native-like structure throughout the beta-domain is itself heterogeneous, involving at least three kinetically distinguishable steps. Residues in loop regions throughout the protein attain persistent structure more slowly than regions of secondary structure. There is in addition evidence for locally misfolded regions of structure that reorganise on much longer timescales. The results reveal that the native state of the protein is generated by the heterogeneous assembly of a series of locally cooperative regions of structure. This observation has many features in common with the findings of recent theoretical simulations of protein folding.